Are nutritional supplements a gateway to doping use in competitive team sports? The roles of achievement goals and motivational regulations - Barkoukis, V.; Lazuras, L.; Ourda, D.; Tsorbatzoudis, H. (Journal of Science and Medicine in Sport, 2020)
Objectives: The study investigated the moderating role of achievement goals and motivation regulations on the association between self-reported nutritional supplement (NS) use, doping likelihood, and self-reported doping behaviour among competitive athletes.